Evaluation of Hepatic Masses Using CT Scan - Padmanaban, Aswin (Asian Journal of Medical Radiological Research, 2021)
Background: The aim is to evaluate hepatic masses using CT scan on 68 adult patients. Subjects and Methods: Sixty- eight adult patients in age ranged 25- 65 years of either gender were selected for this study having hepatic masses. CT images were taken using Siemens 3rd generation spiral CT scan machine. Lesions were mentioned as hyper enhancement, hypo enhancement, iso-dense and mixed enhancement pattern. All the images were studied by single expert radiologist. Results: Out of 68 patients, age group 25- 35 years had 12 male and 7 female, 35- 45 years had 15 male and 11 female, 45- 55 years had 7 male and 6 female and 55-65 years had 6 male and 4 female. Common hepatic masses were liver abscess in 32%, hemangiomas in 5%, focal nodular hyperplasia in 15%, cholangio carcinoma in 4%, metastasis in 6%, simple cysts in 20%, hepatocellular carcinoma in 6 and hydatid cysts in 12%. Sensitivity of CT in detecting hepatic masses found to be100%, specificity 92.2%, positive predictive value (PPV) 96.5% and negative predictive value (NPV) 100%. Conclusion: CT has high diagnostic value in diagnosing cases of hepatic masses.